A study on role of low dose mifepristone in the management of fibroid in reproductive age group women - Rani, Saba; Biswas, Arati; Priya, Shaloo (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Uterine fibroids are the most common benign uterine tumors occurring in 20-50% of women with maximum incidence between 35-45 years of age. Majority of fibroids are asymptomatic. When symptomatic, they present with abnormal menstrual bleeding, dysmenorrhea, chronic pelvic pain, abdominal heaviness, pressure symptoms etc. It is the commonest indication of hysterectomy worldwide. Mifepristone, an antiprogesterone is being widely used as one of the medical managements in potential symptomatic patients (mostly 10-20 mg daily doses). Methods: An institute based prospective study including 100 reproductive aged women with symptomatic single uterine fibroid, was conducted over one-and-a-half-year period. They were administered 10 or 25 mg mifepristone daily for 3 months depending on fibroid size. Clinical parameters were assessed at initiation and at the end of their treatment. Results: Our results showed that mifepristone (both 10 and 25 mg) led to symptomatic relief, with 96% reduction in menstrual blood loss and reversible amenorrhoea in 87% of the patients. Intramural fibroids responded more than submucosal fibroids in terms of relief of menorrhagia and improvement of haemoglobin (Hb) levels, with similar reduction in fibroid volumes of both intramural and submucosal locations. Conclusions: Low dose mifepristone is an effective and safe drug for the medical management of uterine myoma. Due to the benign nature of fibroids, conservative management should be considered wherever feasible. Several clinical trials using 5‑50 mg of mifepristone have been conducted over variable durations between 3-12 months but the exact dosage and treatment duration are yet to be decided.